2014
DOI: 10.1111/jpc.12705
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping: Targeting genotype's rich cousin for diagnosis

Abstract: There are many current and evolving tools to assist clinicians in their daily work of phenotyping. In medicine, the term 'phenotype' is usually taken to mean some deviation from normal morphology, physiology and behaviour. It is ascertained via history, examination and investigations, and a primary aim is diagnosis. Therefore, doctors are, by necessity, expert 'phenotypers'. There is an inherent and partially realised power in phenotypic information that when harnessed can improve patient care. Furthermore, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 21 publications
(24 reference statements)
0
32
0
Order By: Relevance
“…Approximately 32% of the inherited human disorders are associated with atypical craniofacial characteristics [2022]. These “face signatures” (i.e., the face shape difference normalized against age and sex matched controls) can provide the additional clues for clinical diagnoses of genetic syndromes [23, 24]. …”
Section: Dysmorphology Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 32% of the inherited human disorders are associated with atypical craniofacial characteristics [2022]. These “face signatures” (i.e., the face shape difference normalized against age and sex matched controls) can provide the additional clues for clinical diagnoses of genetic syndromes [23, 24]. …”
Section: Dysmorphology Studiesmentioning
confidence: 99%
“…The term “phenotype” in a clinical setting is often used to indicate characteristics that are deviating from the “normal” or typical morphology, physiology, and behavior [24]. This gives rise to questions of what is typical.…”
Section: Phenotypingmentioning
confidence: 99%
“…Proteomics has been defined as “the analysis of the protein complement present in a cell, organ, or organism at any given time [55]”.…”
Section: Defining the Phenotype In Ibdmentioning
confidence: 99%
“…Proteins and/or peptides are generally separated out through gel electrophoresis or liquid chromatography, both of which can be either one- or two-dimensional, and are typically coupled with mass spectrometry. A comprehensive description of current technologies for a proteomics approach to the assessment of biological samples has been published relatively recently [55]. …”
Section: Defining the Phenotype In Ibdmentioning
confidence: 99%
“…Research investigations using Genome Wide Association Study (GWAS) (Network and Pathway Analysis Subgroup of the Psychiatric Genomics Consortium, 2015; Wood, 2013), exome‐based sequencing (Girard et al, 2011; Iossifov et al, 2012; O'Roak et al, 2011; Vissers et al, 2010; Xu et al, 2012), and whole genome sequencing (Kong et al, 2012) techniques have revealed several candidate genes that are associated with common neuropsychiatric disorders such as Autism Spectrum Disorder (ASD), intellectual disability, and schizophrenia. However, in the case of rare disorders, understanding the genetic origins and progressions of disorders—one of the key objectives of Precision Medicine research (Collins & Varmus, 2015; Kohane, 2015; Kohane, Churchill, & Murphy, 2012)—is hindered by small patient population size, the consequent paucity of patient data, and the lack of robust phenotyping protocols (Baynam et al, 2015; Delude, 2015; Robinson, Mungall, & Haendel, 2015). …”
Section: Introductionmentioning
confidence: 99%